More frequent utilization of evidence-based teaching practices leads to increasingly positive student outcomes - Reeves, Philip M.; Bauer, Melanie; Gill, Julia C.; Wang, Cong; Hanauer, David I.; Graham, Mark J. (Frontiers in Education, 2024)
Evidence-based teaching (EBT) practices benefit students, yet our understanding of how frequently these strategies should be utilized in STEM courses is less established. In this study, students (n = 894) of faculty who learned about how to implement EBTs from the Summer Institutes for Scientific Teaching were surveyed. The students rated the frequency of implementation of six types of EBTs after the course and completed a follow-up survey one year later to examine long-term outcomes. Class and student-level analyses indicated that students who reported being exposed to EBTs every couple of classes also reported that they learned more and had a higher ability to work in groups when compared to students who were exposed to EBTs less frequently. The results will help instructors and faculty development professionals understand how frequently EBTs should be incorporated when designing and modifying courses.